Serial intrauterine transfusion for severe fetal anemia due to anti-M alloimmunization - Rachmat Dediat Kapnosa Hasani; Gatot Abdurazak; Adhi Pribadi (Asian Journal of Transfusion Science)
Anti-M antibody is one of the causes of severe fetal anemia and intrauterine death despite its relatively low frequency. A G3P2 26-year-old pregnant woman referred to our hospital at 29 weeks gestational age (WGA) with fetal hydrops. Her second pregnancy results in intrauterine fetal death at 35 WGA due to fetal hydrops. From ultrasound exam, we found singleton live fetus with ascites, cardiomegaly, and pericardial effusion. The peak systolic velocity in the fetal middle cerebral artery (PSV-MCA) was 1.44 multiples of the median corresponding to fetal anemia. The patient’s blood group was B RhD+M− N+. A reactive IgG anti-M antibody was detected at 37°C. Fetal hemoglobin (Hb) from the first cordocentesis was 2.2 g/dl and we perform multiple intrauterine transfusions and cesarean section at 34 WGA. The postdelivery Hb level was 10.2 g/dl and infant need three times packed red blood cell transfusions after delivery.